The Influence of Education Personnel Competence on Student Satisfaction in Educational Services in Higher Education - Pratiwi, Candra; Noor, Irwan; Rozikin, Mochammad (Indonesian Journal of Educational Research and Review, 2024)
The competence of educational personnel in educational institutions plays a crucial role in determining student satisfaction. This is because the competencies of educational personnel in educational institutions are not only related to knowledge and skills in the academic field, but also interpersonal abilities, communication skills, and a willingness to continue learning and developing. This research aims to analyze how much influence the competence of educational personnel has on student satisfaction. The method used is a quantitative method with a type of survey research. The study population consisted of 4,164 students, a sample size of 354 students was obtained. Research data were collected through the dissemination of questionnaires to respondents and then analyzed using SEM-PLS with the help of the SmartPLS application. The results showed that 71.5% of the competency elements of education personnel had a positive and significant influence on student satisfaction. One of the interesting findings of this study is that the personality competence indicator related to the item of consistency in speaking and conveying information obtained the lowest assessment score. This shows that there is a gap in the consistency of communication provided by educational personnel to students. Students may get different information depending on the day and the officer they meet, which can impact their learning experience. Based on these findings, it can be concluded that competency development patterns tailored to individual needs can be an effective strategy in improving certain aspects that influence student satisfaction.